The clinical value of the Controlling Nutritional Status score for predicting prognosis in systolic heart failure cases in the vulnerable phase - Zhao, Jinglin; Xie, Wenli; Ye, Suling; Zhang, Shenglin; Shi, Wenyu; Cui, Ming; Wang, Lili (Frontiers in Nutrition, 2023)
Background: Malnutrition, a commonly encountered complication of heart failure, has an association with poor prognosis. The vulnerable phase of heart failure constitutes the most vulnerable stage of heart failure cases after discharge (usually within 3 months). At present, the prognostic value of controlling nutritional status (CONUT) score in the vulnerable phase of systolic heart failure is unclear. Methods: Totally 187 systolic heart failure cases were retrospectively assessed at the Second Affiliated Hospital of Dalian Medical University. Based on CONUT score at admission, cases were assigned to 3 groups, including the normal nutrition, and mild and moderate or severe malnutrition groups. The primary endpoint was all-cause death in the 90 days following discharge. The secondary, composite outcome encompassed all-cause death and rehospitalization due to heart failure. The independent risk factors for outcome events were obtained by multivariate COX regression analysis. The receiver operating characteristic (ROC) curve analysis and the Delong test were used to compare the prediction performance. Results: During the 90 days of follow-up, 8.6% of HF patients had the primary endpoint and 23.5% had the secondary outcome. All-cause mortality was markedly elevated in the moderate or severe malnutrition group (Logrank: p <0.001). Compared with the normal nutrition group, composite endpoint events had starkly increased incidence rates in both malnutrition groups, and the incidence increased with the severity of malnutrition (Logrank: p <0.05). Multivariate COX risk analysis revealed higher CONUT score (hazard ratio [HR]=1.791, 95% confidence interval [CI] 1.379-2.327), age (HR=1.08, 95%CI 1.028-1.134), B-type natriuretic peptide (BNP) (HR=1.001, 95%CI 1.000-1.001) and aspartate aminotransferase (AST) (HR=1.008, 95%CI 1.001-1.015) at admission as independent predictive factors of all-cause mortality. And higher CONUT score (HR=1.162, 95%CI 1.024-1.318) and lower estimated glomerular filtration rate (eGFR) (HR=0.98, 95%CI 0.966-0.993) for the secondary endpoint. The addition of the CONUT score significantly increased the predictive performance of age, BNP and AST, as well as their combination for all-cause death (Delong test: all p <0.05). Conclusion: The CONUT score at admission independently predicts poor prognosis during the vulnerable phase in patients with systolic heart failure and may be combined with conventional risk factors to further improve the predictive efficacy.